Use of Point of Care Testing (POCT) in measurement of hemoglobin - Yadav, Kapil; Jacob, Olivia Marie; Ahamed, Farhad; Mandal, Manisha; Kant, Shashi (Indian Journal of Community Health, 2018)
Point of care tests (POCT) are critical to success of public health programs like anemia control program which involve measurement of biomarkers; as they help in prompt decision making during first (and in many scenario the only) contact with the targeted beneficiary. There are many methods currently in use for point of care testing for hemoglobin estimation and include manual methods like Sahli’s method, Indirect cyanmethemoglobin method, WHO Hemoglobin Color Scale method; digital hemoglobinometers including the newer non-invasive devices. The current background paper reviewed available published literature regarding performance of different POCT methods for hemoglobin estimation. Available literature indicates that invasive digital hemoglobinometers have shown a reasonable performance for use as POCT in facility and community settings both for clinical diagnosis as well as surveys. Adequate training of front line workers for use of digital hemoglobinometers and adherence to standard operating procedures (SOPs) is essential to reduce errors/biases. Non-invasive digital hemoglobinometers seem to be promising new option for POCT which obviates the need for drawing blood sample (either by venous or capillary method) but further research and development is required before their use in programs.